2008
DOI: 10.5153/sro.1813
|View full text |Cite
|
Sign up to set email alerts
|

Language, Gender and Citizenship: Obstacles in the Path to Learning English for Bangladeshi Women in London's East End

Abstract: A key element of the Government's citizenship strategy is the requirement that all immigrants have a basic command of English. The lack of English speaking skills has been identified as a contributory factor to much of the social unrest amongst different communities in the UK. It has been argued that the ability to speak English will allow immigrants to integrate better, create more cohesive communities and reduce segregation. This paper will question the emphasis placed on language proficiency in reducing seg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The research findings also signal the complex factors that influence the process of learning a new language. Ahmed (2008) has shown this in relation to Bangladeshi women in London who provide valuable childcare and support for families so that men can become active citizens. They are not likely to meet or socialise with English speakers whilst looking after children and many of their social contacts will be with other Bangladeshi women in community centres where little English is spoken.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The research findings also signal the complex factors that influence the process of learning a new language. Ahmed (2008) has shown this in relation to Bangladeshi women in London who provide valuable childcare and support for families so that men can become active citizens. They are not likely to meet or socialise with English speakers whilst looking after children and many of their social contacts will be with other Bangladeshi women in community centres where little English is spoken.…”
Section: Resultsmentioning
confidence: 98%
“…Participants in this group gave various reasons for not having more frequent contact with English speakers, including those mentioned above in relation to the lack of suitable classes, their views about the values of people from other communities and their age. When classes became available, men were more likely to go to them as women were seen as being responsible for looking after any children and their male partners needed English to get work (see also Ahmed, 2008 for evidence of the gendered nature of access to English language learning). People in this group wanted to return or had wanted to return to Poland when they first came.…”
Section: Language Network and Integrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Inequalities both 'inside' and 'outside' of the process that shape migrant women's experiences of naturalization have been documented and the withdrawal of state support criticized during the course of our project in the Wonder Foundation (2016) report. This work builds on a longstanding body of research demonstrating the intersections of race and gender inequality, lack of language proficiency and socioeconomic deprivation for some migrant women and the role of ESOL in this process (Ahmed 2008). Some migrant women already face a 'triple burden' as female, foreign and racialized -in addition to women's 'double burden' of unpaid work in the home and labour market (Pessar 1999).…”
Section: Anxious Citizensmentioning
confidence: 99%
“…173 Older Bangladeshi and Pakistani women may be prevented from acquiring English proficiency through family obligations or cultural and community expectations. 174 A number of studies have suggested that language discordance in clinical encounters may negatively impact on quality of care. 172,[175][176][177] Challenges in communicating in language-discordant consultations can lead to particularly strong tensions between 'ideal' standards of communication and what is 'good enough'.…”
Section: Overall Conclusionmentioning
confidence: 99%